IMPLEMENTASI PENGGUNAAN MODUL TRIGONOMETRI DENGAN PENDEKATAN PENEMUAN TERBIMBING TERHADAP MINAT BELAJAR SISWA KELAS X - Indah Nopita Sari; Krisdianto Hadiprasetyo; Erika Laras Astutiningtyas (UNIVERSITAS TANJUNGPURA, 2022)
This research includes descriptive research with a qualitative approach. The subjects in this study were mathematics teachers, and class X students of SMK Bina Patria 1 Sukoharjo in the 2021/2022 academic year. The object of this research is the implementation of the use of a trigonometry module with a guided discovery approach to students' interest in learning. Data collection techniques using interviews and questionnaires. From the results of research conducted, students' interest in learning obtained an average percentage on the aspect of feeling happy of 70.44% including the